PURIFIKASI BIOGAS BERBASIS ABSORBENT ZEOLIT DIAKTIVASI KOH, DAN NAOH TERHADAP KUALITAS BIOGAS - Farid Majedi; Agus Choirul Arifin; Indah Puspitasari; Shofyan Dwi Saputro; Septian Nurfaranto (Jurnal Teknologi, 2022)
Fossil fuel reserves are increasingly depleting and non-renewable. The choice of utilizing alternative energy sources that are renewable and environmentally friendly is a very smart thing to do. Biogas is a renewable energy and is environmentally friendly and inexpensive. The element CO2 can interfere with the combustion process. To increase the quality of biogas, it is possible to reduce the interfering CO2 element in the process. Purification is one way to purify the CO2 content of biogas. Burning. In this study, biogas purification was carried out by absorbing carbon dioxide (CO2) using zeolite which was activated by heat treatment of 300oC and Potassium Hydroxide (KOH) and Sodium Hydroxide (NaOH) solution, namely by varying the flow rate of biogas entering the purifier. The test was carried out on 4 variables, namely non-purified biogas, at a rate of 3 l/m, a rate of 5 l/m, and a rate of 7 l/m. Based on this study, the results obtained, the greater the flow rate of biogas, the lower the CO2 content and the higher the CH4 content. The lowest CO2 content at variablel 5 L/minute was 2952.78 ppm. The highest content of CH4 is 45845.25 ppm at 7 L/minute. The best condition of this research is the flow speed variable of 7 L/min with CH4 and CO2 content of 45845.25 ppm and 2967 ppm.